The fourth national tuberculosis prevalence survey in Myanmar. - Si Thu Aung; Wint Wint Nyunt; Myat Myat Moe; Htin Lin Aung; Thandar Lwin (Public Library of Science (PLoS), 2022)
Tuberculosis (TB) remains a significant cause of morbidity and mortality in Myanmar. The fourth National TB Prevalence Survey was conducted in 2017-2018 to determine the actual burden of TB not only at the national level but also for three subnational strata (the states, regions other than Yangon, and the Yangon region) and develop a more efficacious country strategy on TB care and control. One hundred and thirty eight clusters were selected by population proportionate sampling. Adult (≥15 years of age) residents having lived for 2 weeks or more in the households of the selected clusters were invited to participate in the survey. The survey participants were screened for TB by a questionnaire and digital chest X-ray (CXR) after providing written informed consent. Individuals with a positive symptom screen and/or chest X-ray suggestive of TB were asked to provide sputum samples to test for Mycobacterium tuberculosis (Mtb) by Ziehl-Neelsen direct light microscopy, Xpert MTB/RIF Ultra (Xpert), and culture (Ogawa media). Bacteriologically confirmed TB cases were defined by an expert panel. Of 75 676 eligible residents, 66 480 (88%) participated, and 10 082 (15%) screened positive for TB. Among these, 322 participants were defined as bacteriologically confirmed TB cases. Cough lasting for two weeks or longer, one of the criteria used for screening for symptoms, could detect only 14% (45/322) of the study cases. The estimated prevalence of bacteriologically confirmed adult pulmonary TB was 468 (95% CI: 391-546) per 100,000. The prevalence was much higher among males, the older age group, urban Yangon and remote villages. In-depth interview with the participants on TB treatment showed that none of them was diagnosed in a TB health centre (primary care facilities). The prevalence of TB in Myanmar is still high due to challenges such as uncontrolled urbanization, an ageing population, migration, and poor access to health facilities in remote areas. New screening and diagnostic tools might help to detect more TB patients. There is a need to lay greater emphasis on multisectoral approaches, decentralization and the integration of basic TB services into primary care facilities.